Diabetes education through group classes leads to better care and outcomes than individual counselling in adults: A population-based cohort study - Hwee, Jeremiah (Can J Public Health, 2014)
OBJECTIVE: Self-management education, supported by multidisciplinary health care teams, is essential for optimal diabetes management. We sought to determine whether acute diabetes complications or quality of care differed for patients in routine clinical care when their self-management education was delivered through group diabetes education classes versus individual counselling. METHODS: With the use of population-level administrative and primary data, all diabetic patients in Ontario who attended a self-management education program in 2006 were identified and grouped according to whether they attended group classes (n=12,234), individual counselling (n=55,761) or a mixture of both (n=9,829). Acute complications and quality of care in the following year were compared among groups. RESULTS: Compared with those attending individual counselling, patients who attended group classes were less likely to have emergency department visits for hypo/hyperglycemia (odds ratio 0.54, 95% confidence interval [CI]: 0.42–0.68), hypo/hyperglycemia hospitalizations (OR 0.49, CI: 0.32–0.75) or foot ulcers/cellulitis (OR 0.64, CI: 0.50–0.81). They were more likely to have adequate HbA1c testing (OR 1.10, CI: 1.05–1.15) and lipid testing (OR 1.25, CI: 1.19–1.32), and were more likely to receive statins (OR 1.22, CI: 1.07–1.39). CONCLUSION: Group self-management education was associated with fewer acute complications and some improvements in processes of care. Group sessions can offer care to more patients with reduced human resource requirements. With increased pressure to find efficiencies in health care delivery, group diabetes education may provide an opportunity to deliver less resource-intensive care that simultaneously improves patient care.